Spectroscopic Properties of 4-Halo-2-(4-chlorophenyliminomethyl)phenol and 4-Halo-2-(4-bromophenyliminomethyl)phenol - Unver, Huseyin; Karakas, Asli; Colak, Naki; Cakır, Bekir; Yuksel, Huseyin; Mehmet Zengin, D. (Asian Journal of Chemistry, 2012)
4-Halo-2-(4-chlorophenyliminomethyl)phenol and 4-halo-2-(4-bromophenyliminomethyl)phenol have been synthesized and then characterized by elemental analysis, FTIR, 1H NMR and UV- Vis spectroscopy. The spectroscopic data of all the investigated com¬pounds revealed that the tautomeric equilibrium of the studied Schiff bases favour the enol form.